Effectiveness of Brand Image and Brand Awareness in Improving the Performance of the West Java Provincial Centre for Teachers and Education Personnel through Social Media Engagement - Yuli Rianawati; Kosasih Kosasih; Yuyun Yuniarsih (Jurnal Ilmiah Global Education, 2026)
The current era of digitalisation has brought about changes in public communication within government institutions. This is also the case at the West Java Provincial Teacher and Education Personnel Centre (BBGTK Jabar), which is the technical implementation centre of the Ministry of Primary and Secondary Education (Kemendikdasmen) tasked with providing training and competency development for teachers and education personnel in the province of West Java. Public communication plays a role in every activity carried out by this institution. This study aims to analyse the positive and effective influence of endogenous variables, namely brand image and brand awareness, on exogenous variables, namely the performance of BBGTK Jabar, through social media engagement as a mediating variable. The type of research used is descriptive and verificative with an explanatory survey research method. The data used are primary and secondary data, where the primary data collection technique is through surveys, while secondary data are obtained through literature studies, journals, articles, and websites. The research population was determined using the Slovin formula with a margin of error of 10%, resulting in 100 respondents consisting of teachers and educational staff who are active users of BBGTK Jabar social media. The research instrument was measured using a 5-point Likert scale, and data analysis was performed using Structural Equation Modelling (SEM). The results of the analysis show that brand image and brand awareness have a direct positive and effective influence on BBGTK Jabar performance through social media engagement as a mediating variable.